Kemampuan Prediksi Nilai Ebtanas Murni SMP dan IQ terhadap Prestasi Belajar di SMU - M.I. Sri Widadi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Predictability of the National Final Examination Score in Secondary Schools and intelligence quotient to Students' Achievement in Senior High Schools. The aim of this study was to determine the ability of the Ebtanas score (NEM) and intelligence quotient (IQ) to predict students achievement in Senior High Schools. The data were obtained from the existing documents of the public SMUs in Surakarta Municipality, and were then analyzed by regression technique. The result showed that the NEM could be used to predict students achievement in Senior High Schools, whereas the IQ couldnot. The NEM seemed to be considered as an entry behavior and prerequisite for higher learning. Therefore, it could be suggested that the selection of students should be based on the NEM obtained from the lower level of education rather than on students' IQ.